KINERJA BIDANG PENGELOLAAN PENDAPATAN DAERAH BADAN KEUANGAN DAERAH PROVINSI KALIMANTAN SELATAN - Ade Hermawan; Muhammad Jamili; Bakhtiar Bakhtiar (UPT Publikasi Dan Pengelolaan Jurnal Universitas Islam Kalimantan MAB Banjarmasin, 2023)
The Regional Revenue Management Sector of the Regional Financial Agency of South Kalimantan Province has good accountability, is able to fulfill financial obligations well, has good honesty, applies the principles of efficiency and effectiveness well, and control activities are carried out well too. So overall it can be concluded that the performance of the Regional Revenue Management Sector of the Regional Financial Agency of South Kalimantan Province all leads to good performance.